A Primer on School Budgeting - Kratz, Robert N.; Scott, Charles A.; Zechman, Harry T. (Rowman & Littlefield Publishers, 1998)
Does the prospect of preparing your school district's budget seem daunting? Beginning school administrators, often having only one theoretical course on the subject under their belt, see the budget development process as a nightmare. New administrators, teachers, and board members who have little experience with budgeting are justifiably concerned by the prospect of their involvement in budgeting. This book leads the reader through all stages of the process, from the theoretical underpinnings (history, types of budgets, etc.) and practical considerations (revenue planning, budget calendar, etc.) through to the adoption of the budget and its implementation. Includes sample budgets, and tips for administration of a budget once it is in place.